The options course : high profit & low stress trading methods - Fontanills, George (John Wiley & Sons, 2005)
Use this invaluable tool to gain a competitive edge and avert bad investment decisions. Well-known options strategist and instructor George Fontanills has updated his time-tested and bestselling book, The Options Course. The new edition improves and expands upon the original to help you avoid some common and costly options mistakes.